PENGGUNAAN MEDIA AUDIOVISUAL UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN KETERAMPILAN MATERI ANYAM KERTAS SISWA KELAS VIII D MTs NEGERI TARUSAN PESISIR SELATAN - SYAMSUARLI, Drs. Efrizal, M.Pd, Drs. Erwin A, M.Sn (Serupa The Journal of Art Education, 2014)
This study aimed to determine the improvement of student learningoutcomes with the use of audiovisual media use on skill learning materials woven paper material. Classroom action research was carried out by 2 cycles with steps of planning, action, observation and reflection. Means of collecting data using observation sheets, teacher observation sheet, observation sheets and student learning outcomes assessment format. The research data obtained showed an increase in the data processing to an increase in learning outcomes. Average learning outcomes in the first cycle and the second cycle 69.57 gained an average of 78.14 learning outcomes. The revenues resulted this study showed a significant increase as a result of the actions that have been performed, the second cycle of learning outcomes already are above KKM.Keywords : learning outcomes, audiovisual of media